(3eONd Edi GdefgLjI GdeJcGedI dEOGQI GdLhOI GdTGedI (B:s (3O hLgI fXQ (B/s - (3Ybjdj, YeQ hUajs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2001)
(3GHYGO EOGQI GdLhOI GdTGedI(B-(3GdefgLjI GdeJcGedI dEOGQI GdLhOI GdTGedI(B-(3feGPL eNJGQI Yf EOGQI GdLhOI GdTGedI hGdCNWGA GdTGFYI aj JWHjagG HQfGeL ebJQM dJNWjW GdLhOI heTQhY LGFRI GOGQI GdLhOI GdTGedIs
Keywords: (3EOGQI GdEfJGLs; (3VHW GdLhOI, LhOI GdEfJGLs